Cannabidiol for neurodegenerative disorders: A comprehensive review - Bhunia, Sukanya; Kolishetti, Nagesh; Arias, Adriana Yndart; Vashist, Arti; Nair, Madhavan (Frontiers in Pharmacology, 2022)
Despite the significant advances in neurology, the cure for neurodegenerative conditions remains a formidable task to date. Among various factors arising from the complex etiology of neurodegenerative diseases, neuroinflammation, and oxidative stress play a major role in pathogenesis. To this end, some phytocannabinoids isolated from Cannabis sativa (widely known as marijuana) have attracted significant attention as potential neuro-therapeutics. The profound effect of ∆9-tetrahydrocannabinol (THC), the major psychoactive component of Cannabis, has led to the discovery of the endocannabinoid system as a molecular target in CNS. Cannabidiol (CBD), the major non-psychoactive component of Cannabis has recently emerged as a potential prototype for neuroprotective drug development due to its antioxidant and anti-inflammatory properties as well as its well-tolerated pharmacological behavior. This review briefly discusses the role of inflammation and oxidative stress in neurodegeneration and demonstrates the neuroprotective effect of CBD highlighting its general mechanism of action and disease-specific pathways in Parkinson’s diseases (PD) & Alzheimer’s diseases (AD). Furthermore, we have summarized the preclinical and clinical findings on the therapeutic promise of CBD in PD AD, shed light on the importance of determining its therapeutic window, and provided insight to identify promising new research directions.